Pengaruh Bimbingan Kelompok Terhadap Minat Belajar Siswa SMP N 3 Lubuk Sikaping - Sriwahyuni, Aprima; Yusri, Fadhilla; Afrinaldi; Rahmi, Alfi; Pratama, Andy Riski (Program Studi Magister Pendidikan Agama Islam, 2024)
This research is a pre-experimental research with a one group pre-test and post-test research design. The population in this study was 116 students and a research sample of 8 people was taken, using a purposive sampling technique, sampling based on considerations of student learning boredom. The technique for collecting data in this research is the Likert scale. Meanwhile, the data analysis technique in this research is the Wilcoxon signed rank test method with the help of Statistical Product And Service Solutions (SPSS) version 22. The research results are from the Wilcoxon (Z) value which shows that there is a difference between the pre-test and post-test. From the results of the Wilcoxon test calculation, the asymp sig value (0.012) is obtained, which means it is smaller than <a (a=0.05), which means Ha is accepted and Ho is rejected. From the results of the Wilcoxon test calculations, it can be concluded that there is an increase in students' interest in learning at SMP N 3 Lubuk Suhuing through group tutoring services. Based on the research results, the results of interest in learning before treatment (Pretest) were obtained, namely a mean of 179.12, which is classified as in the medium category. Meanwhile, after the treatment (Posttest), the mean was 201.25, which is classified as high. Pretest and Posttest hypothesis testing, if converted to the Z value then the value is -2.521, the sig or p-value is 0.012 then Ha is accepted Ho is rejected, so there is a difference in students' interest in learning before and after being given treatment, namely group guidance services. This means that group guidance services have an influence on students' interest in learning at SMP N 3 Lubuk Sikaping. Abstrak Penelitian ini merupakan penelitian pre-eksperimen dengan desain penelitian one group pre-test dan post-test. Populasi pada penelitian ini yaitu 116 siswa dan sampel penelitian sebanyak 8 orang diambil, dengan teknik purposive sampling, pengambilan sampel berdasarkan pertimbangan dari kejenuhan belajar siswa. Teknik dalam pengumpulan data pada penelitian ini yaitu skala likert. Sedangkan teknik analisis data dalam penelitian ini yaitu metode Wilcoxon signed rank test dengan bantuan Statistical Product And Service Solutions (SPSS) versi 22. Hasil penelitian dari nilai Wilcoxon (Z) yang menunjukkan adanya perbedaan antara pre-test dan post-test. Dari hasil perhitungan uji Wilcoxon diperoleh nilai asymp sig (0,012), yang artinya lebih kecil < a (a=0,05) yang berarti Ha diterima dan Ho ditolak. Dari hasil perhitungan uji Wilcoxon dapat disimpulkan bahwa terdapat peningkatan minat belajar siswa di SMP N 3 Lubuk Sikaping melalui layanan bimbingan kelompok. Beradsarkan hasil penelitian diperoleh hasil minat belajar sebelum perlakuan (Pretest) yaitu mean 179.12 ini tergolong pada kategori sedang. Sedangkan setalah dilakukan perlakuan (Posttest) meannya menjadi 201.25 ini tergolong pada kategori tinggi. Uji hipotesis Pretest dan Posttest, apabila dikonversikan ke nilai Z maka besarnya -2.521, nilai sig atau p-value sebesar 0,012 maka Ha diterima Ho ditolak, sehingga ada perbedaan minat belajar siswa sebelum dan sesudah diberikan perlakuan yaitu layanan bimbingan kelompok. Artinya layanan bimbingan kelompok berpengaruh terhadap minat belajar siswa SMP N 3 Lubuk Sikaping.